SAP HANA Data Management and Performance on IBM Power Systems - Quintero, Dino; Bull, Damon; Cardoso, Vinicius; Freire, Cleiton; Kass, Eric (IBM Redbooks, 2020)
This IBM® Redpaper Redbooks publication provides information and concepts about how to take advantage of SAP HANA and IBM Power Systems features to manage data and performance efficiently. The target audience of this book includes architects, IT specialists, and systems administrators who deploy SAP HANA and manage data and SAP system performance.
Online resource; Title from title page (viewed April 1, 2020)
Keywords: SAP HANA (Electronic resource); IBM Power systems; Information technology -- Management; Database management; Business enterprises -- Data processing; Technologie de l'information; Gestion; Bases de données; Gestion; Entreprises; Informatique; Information technology; Management; Business enterprises; Data processing